CARTOGRAPHIC IDEALIZATION OF THE EARTH'S SURFACE AND ITS ROLE IN RELIEF STRUCTURE STUDY (Scientific journal of the Fergana State University, 2024)
In the article, the methodological basis of the systematic approach was used in the analysis of the current Amudarya delta. The method of relief plastic, which is considered one of the methodological foundations, was used. On topographic maps we show the elevations and depressions of the relief and these elevations and depressions form a basin, or a relief plastic map shows the structure of each landform. The relief structure of the current Amudarya delta is a product of surface water flows.  As a result of revealing their common and important features by creating idealized images, we have revealed simplified concepts about real objects, in particular, the relief paintings of the current Amudarya delta.